The Effectiveness of Small Business Management in Promoting the Competitiveness of MSMEs in Bone Regency - Nurul Ayuni; Andi Adhe Amalya; Ahmad Difa Awlia (PT. Caesarindo Triloka Persada, 2026)
This study aims to analyze the effectiveness of small business management policies in promoting the competitiveness of Micro, Small, and Medium Enterprises (MSMEs) in Bone Regency. Employing a qualitative approach with descriptive methods, this research utilizes data obtained through literature studies, in-depth interviews, and policy document reviews. The analysis is grounded in Sutrisno’s effectiveness theory, assessing three key indicators: program understanding, target accuracy, and tangible change. The findings indicate that the management of small businesses in Bone Regency is not yet optimal. In terms of program understanding, many business owners lack awareness of government facilities and the Online Single Submission (OSS) licensing system due to limited digital literacy. Regarding target accuracy, policies largely focus on micro-enterprises, resulting in a lack of intervention for small businesses that remain vulnerable to market fluctuations. Furthermore, no tangible changes were observed regarding business scale transitions or capacity improvements. The study recommends that the local government strengthen NIB or OSS-based data collection and develop tiered assistance packages to ensure more inclusive and sustainable economic growth.